2021
DOI: 10.3390/ani11040979
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins from Lactic Acid Bacteria. A Powerful Alternative as Antimicrobials, Probiotics, and Immunomodulators in Veterinary Medicine

Abstract: In the search for an alternative treatment to reduce antimicrobial resistance, bacteriocins shine a light on reducing this problem in public and animal health. Bacteriocins are peptides synthesized by bacteria that can inhibit the growth of other bacteria and fungi, parasites, and viruses. Lactic acid bacteria (LAB) are a group of bacteria that produce bacteriocins; their mechanism of action can replace antibiotics and prevent bacterial resistance. In veterinary medicine, LAB and bacteriocins have been used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 160 publications
1
83
0
Order By: Relevance
“…Many studies reported α-glucosidase inhibition activity ( Khan et al, 2017 ), production of bacteriocins (protein compounds) which have antagonistic potential against pathogenic bacteria, and a different degradation system in the digestive system ( Hawaz, 2014 ). Hernández-González et al (2021) also studied the antimicrobial, probiotics, and immunomodulatory potential of LAB in veterinary medicine. Moreover, several studies have documented the antibacterial effects of probiotics as antagonistic bacteria against Gram-negative and Gram-positive pathogenic bacteria such as E. coli , P. aeruginosa and S. aureus and proved that probiotics can be used as antimicrobial agents instead of antibiotics to minimize antibiotics resistance ( Sharafi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported α-glucosidase inhibition activity ( Khan et al, 2017 ), production of bacteriocins (protein compounds) which have antagonistic potential against pathogenic bacteria, and a different degradation system in the digestive system ( Hawaz, 2014 ). Hernández-González et al (2021) also studied the antimicrobial, probiotics, and immunomodulatory potential of LAB in veterinary medicine. Moreover, several studies have documented the antibacterial effects of probiotics as antagonistic bacteria against Gram-negative and Gram-positive pathogenic bacteria such as E. coli , P. aeruginosa and S. aureus and proved that probiotics can be used as antimicrobial agents instead of antibiotics to minimize antibiotics resistance ( Sharafi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…class Ib (labyrinthopeptins): it regroups globular and inflexible bacteriocins that are negatively charged or with no net charge. These bacteriocins can inhibit catalytic enzymes crucial for the proliferation of susceptible bacteria [37].…”
Section: Classificationmentioning
confidence: 99%
“…The fermentation process has also been found to elicit a beneficial effect on reducing the content of anti-nutritional factors (ANFs), e.g., phytates and protease inhibitors, in plant products [18]. In addition, LAB have the ability to produce antimicrobial substances called bacteriocins, which are ribosome-synthesized peptides that exhibit antimicrobial activity, can inhibit pathogenic microflora in food [7,43,44], and are usually secreted outside the bacterial cell. Bacteriocins synthesized by LAB strains, including those of the genera Lactococcus sp., Lactobacillus sp., Pediococcus sp., Carnobacterium sp., or Leuconostoc sp., are considered safe to be used in food production [32,45,46].…”
Section: Fermentation With Labmentioning
confidence: 99%